Doctor-patient relationship in the diagnosis and treatment of neoplasmatic diseases - Jaracz, Katarzyna; Jaracz, Marcin (Journal of Education, Health and Sport, 2019)
Neoplasmatic diseases, due to their chronic character, as well as the potential threat to life and other important values, are a significant life stressor. An important factor in their treatment is the patients’ advantageous psychological adaptation to the disease. This, apart from the patient-centered factors, strongly relies on effective and satisfying communication between a physician and patient. Application of patient-focused approach in the treatment process enables regarding patient’s expectations as for information and emotional support, which is essential for obtaining patients’ compliance during the treatment course. Evolution of approaches to patient-physician communication, as well as the current understanding of this process, were reviewed and discussed in the paper. Patients’ preferences concerning process of communication with oncologist were described. Studies presenting the influence of patient-physician communication on the treatment process, were discussed. The importance of patient’s satisfaction with relationship with a physician for successful treatment of a neoplasmatic disease is depicted. Significance of appropriate communication in palliative care was stressed, with special regard to communication of breaking bad news. Factors negatively influencing patient-physician communication in oncology were characterised. Methods of training communication skills in oncology were briefly presented.